STATISTICS IN SERVICE QUALITY ASSESSMENT - Dragana Gardašević; Srđan Kružević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
For any quality evaluation in sports, science, education, and so, it is useful to collect data to construct a strategy to improve the quality of services offered to the user. For this purpose, we use statistical software packages for data processing data collected in order to increase customer satisfaction. The principle is demonstrated by the example of the level of student satisfaction ratings Belgrade Polytechnic (as users) the quality of institutions (Belgrade Polytechnic). Here, the emphasis on statistical analysis as a tool for quality control in order to improve the same, and not the interpretation of results. Therefore, the above can be used as a model in sport to improve the overall results.